Thermomechanical Process Simulation to Predict Processing of Mechanical Properties of Alloys Al-Zn-Mg-Cu - Marian-Iulian NEACSU; Elisabeta VASILESCU; Doru HANGANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2013)
This paper presents how to perform simulation (prediction) mechanical properties of aluminum alloys of the system Al-Zn-Mg-Cu. Graphical interface that can predict the mechanical properties studied was performed using MATLAB software version 6.5 based on mathematical equations mathematical models obtained by the mathematical modeling of thermomechanical treatment process studied. This GUI can be established before the thermomechanical treatment parameters to achieve a favorable complex mechanical properties.